2009
DOI: 10.1111/j.1752-8062.2009.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Networks of Obesity and Type 2 Diabetes in Rural Appalachia

Abstract: The prevalence of obesity and diabetes has been studied in adolescent and adult populations in poor, medically underserved rural Appalachia of West Virginia. A web-based questionnaire about obesity and diabetes was obtained in 989 family members of 210 Community Based Clinical Research (CBPR) trained adolescent members of a network of 18 science clubs, incorporating 142 families. After age-correction in <20 years old, 50% of both adolescents and adults were obese. The frequency distribution of obesity was trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…There have been a number of studies of this region that have shown that Appalachia is a region that has one of the highest obesity rates in the nation. 28,29 In addition, individuals living in this region are at greater risk for cardiovascular disease 30,31 , diabetes 20,21 , lung diseases 3234 , and several types of cancer 30,32,33,35 , relative to individuals in other areas. Some reasons for this may be the general lack of education in this region, low socioeconomic status, unemployment, lack of access to care, and lack of infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies of this region that have shown that Appalachia is a region that has one of the highest obesity rates in the nation. 28,29 In addition, individuals living in this region are at greater risk for cardiovascular disease 30,31 , diabetes 20,21 , lung diseases 3234 , and several types of cancer 30,32,33,35 , relative to individuals in other areas. Some reasons for this may be the general lack of education in this region, low socioeconomic status, unemployment, lack of access to care, and lack of infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding what is known about obesity and depression management in primary care centers in Appalachia is consistent with the most recent priorities set forth by the National Institutes of Health and Healthy People 2020, which puts emphasis on understanding relationships between psychosocial and behavioral determinants of health and chronic illnesses in groups that experience health disparities (Pancoska et al., ). Understanding what influences the health and function of Appalachian adults is essential so that both healthcare providers and policymakers can appropriately meet patient needs.…”
Section: Screening Practices In Appalachiamentioning
confidence: 61%
“…Risk of obesity has been found to increase with decreased income and increased in age among Appalachians (Amarasinghe, D'Souza, Brown, Oh, & Borisova, 2009). In addition, obese Appalachian residents living in distressed counties with high poverty and high unemployment rates are diagnosed with diabetes at a much earlier early age (Barker et al, 2011;Pancoska et al, 2009). Health disparities in Appalachia appear to be uniquely associated with culture, economic, and geographical characteristics (Hutson, Dorgan, Phillips, & Behringer,2007).…”
Section: Defining the Appalachian Regionmentioning
confidence: 99%